Azafullerenes encapsulated within single-walled carbon nanotubes - Pagona, G; Rotas, G; Khlobystov, A; Chamberlain, T; Porfyrakis, K; Tagmatarchis, N (2008)
Methods of insertion of azafullerenes in single-walled carbon nanotubes (SWNTs) at different temperatures were investigated, while the effects of the conditions applied on the structure of azafullerene-based peapods, namely, C59N@SWNTs, were explored. Morphological characteristics of C59N@SWNTs were assessed and evaluated by means of high-resolution transmission electron microscopy (HR-TEM). Pathways and chemical reactions that occur upon encapsulation of C59N within SWNTs were evaluated. Monomeric azafullerenyl radical C59N• as inserted into SWNTs at high temperature, from purified (C59N)2 in the gas phase, can undergo a variety of different transformations forming dimers, oligomers or existing in its monomeric form inside SWNTs due to the stabilization effect by nanotube side walls. However, under milder conditions, that is, at lower temperature, bisazafullerene (C59N)2 can be inserted into SWNTs in its pristine dimeric form. Copyright © 2008 American Chemical Society.